Alternative unfired binders as lime replacement in hemp concrete. (30th April 2020) - Haik, R.; Bar-Nes, G.; Peled, A.; Meir, I.A.
Highlights: Replacing the lime in LHC with five different alternative binders was investigated. Lime replacement with an unfired binder is expected to save EE, EC, and costs. At its optimal concentration, the alternative binder, improved LHC strength and water resistance. The thermal properties of the LHC were hardly affected by the lime replacement. Abstract: The objective of this research was to develop sustainable building materials based on lime hemp concrete (LHC) by replacing some or all of the lime with different dosages of alternative unfired binders, namely, clay, limestone or basalt. The compressive strength, thermal properties and water resistance of mixtures of lime and the unfired binders, with and without hemp, were investigated. In general, for mixtures without hemp, replacing 50% of the lime with an alternative binder resulted in a reduction in the compressive strength. However, when hemp was added, an optimal content of alternative binder was found, up to which a higher content of alternative binder led to improved properties (compressive strength and water resistance), but beyond which there was impairment of the properties. In summary, the higher the content of the alternative binder, the greater the LHC strength, while the density remains the same; however, at too low a lime content (here 10% of the binder material) there was not enough lime to facilitate the formation of a continuous binding matrix within the sample, leading to a reduction in strength. Finally, the thermal properties of LHC were almost not affected by the replacement of the lime with an alternative binder.